Effects of an exercise system on improving paddling technique in young kayakers (RIAF. International Journal of Physical Activity, 2024)
This research addresses the impact of an exercise system on the improvement of the stroke in canoeists of the Ecuadorian Canoeing Federation. The objective is to demonstrate the effectiveness of the exercise system for the improvement of the stroke technique in athletes of the junior and senior categories. The research is of experimental modality, with a pre-experimental design of quantitative approach, with a single group (N = 12) of population. The exercise system has a three-stage structure consisting of: planning, implementation, control and evaluation of the exercises; which is based on the measurement methods with the application of the static execution test, stroke technique and the 50-meter speed test in the canoe. The results were corroborated with the application of the hypothesis tests of the Wilcoxon signed ranks and the T student test, which by the levels of significance demonstrated the favorable differences between the two measurements (pretest and posttest).
Keywords: System; exercises; technique; canoe